Beyond the Religious Authority: A Genealogy Analysis of Leaders’ Legitimacy in Indonesian Islamic Communities - Akmal Mundiri; Tiara Nurul Annisa’ (Al-Qalam Institute, 2025)
The authority of the kyais in Islamic boarding schools today cannot be fully understood solely through traditional theories that focus on knowledge and sanad. In the contemporary context, the legitimacy of kyais is also influenced by factors such as social relations, descent and digital media. This study aims to analyze the process by which the authority of the kyais is established in the Islamic boarding school community. The method used is qualitative, with a case study approach, and data collection through in-depth interviews, direct observation, and document analysis. The results of the study show that the process of establishing the authority of the kyais in the Islamic boarding school community is carried out through scientific genealogy (sanad keilmuan), genealogy of descent (nasab/dzurriyah), and adaptation to modernity through social media and digital public spaces. These findings show that the authority of the kyais is not fixed but is shaped through a social process that continues to change alongside the use of digital media, symbols, and cultural interactions.